2015
DOI: 10.1007/s11249-014-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Tribochemical Products of Hydrogenated DLC Film and Stainless Steel Pair in Air Detected by Mass Spectrometry

Abstract: A technique for detecting gaseous products in an air atmosphere was achieved based on a quadrupole mass spectrometer and a space-minimized sliding unit settled in a vacuum chamber for the purpose of controlling the flow of sample gas and increasing the concentration of products. The test results showed that when a hydrogenated DLC film was rubbed in a dry air environment, carbons were oxidized to form CO 2 . However, in a humid air atmosphere, water molecules competitively reacted with carbons to form hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In dry oxygen and dry air, much deeper wear tracks (60−90 nm) were created on H-DLC (Figure 5). Based on the previous findings about the easy oxidation of the H-DLC surface and the wear susceptibility of the oxidized surface layer, 5,7,8 the increase in H-DLC wear in O 2 and air environments can be attributed to the combined actions of continuous surface oxidation by oxygen and repeated removal of the oxidation product by interfacial shear during sliding. The wear of H-DLC substrate in dry O 2 and dry air was accompanied by the SS counter-surface wear.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In dry oxygen and dry air, much deeper wear tracks (60−90 nm) were created on H-DLC (Figure 5). Based on the previous findings about the easy oxidation of the H-DLC surface and the wear susceptibility of the oxidized surface layer, 5,7,8 the increase in H-DLC wear in O 2 and air environments can be attributed to the combined actions of continuous surface oxidation by oxygen and repeated removal of the oxidation product by interfacial shear during sliding. The wear of H-DLC substrate in dry O 2 and dry air was accompanied by the SS counter-surface wear.…”
Section: Resultsmentioning
confidence: 93%
“…In the presence of oxygen, continuous formation of oxide layers and their removal by the counter surface result in significant H-DLC wear. 44 This is evident by the significantly higher wear rate in dry oxygen (P O2 = 760 Torr) compared to dry air (P O2 = 152 Torr), indicating that the amount of oxygen in the environment plays a critical role. Removal of the oxidized layers from the DLC surface produces wear debris that can have abrasive effect on the counter surface resulting in mutual wear of both surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it has been noted that wear of CN X and DLC coatings increases with increasing oxygen levels because of the reactions that occur between the coating and the oxygen molecules [13,14]. Xu et al reported that the tribochemical reactions of DLC coatings in dry air led to oxidation of carbon, resulting in the formation of CO 2 [25]. The structure of worn CN X changes from that of the deposited CN X because of desorption of nitrogen atoms inside the coating [10].…”
Section: The Roles Of Water and Oxygen Molecules Inmentioning
confidence: 99%